Effect of whole body vibration during static squats on the myoelectrical properties of the vastus lateralis - Robbins, D.; Goss-Sampson, M. (International Journal of Sports Science, 2013)
The effects of whole body vibration (WBV) on EMG timing, frequency and amplitude have previously been studied, however to best of the authors knowledge there have been no studies on the effect of WBV on the conduction velocity of myoelectrical signals. Muscle fibre conduction velocity, EMG frequency and amplitude of the vastus lateralis were therefore assessed in twelve male participants (1.81 +/- 0.1 m, 82.2 +/- 10.7 kg, 25.4 +/- 4.0 years) at the start and end of partial static squats, both with and without WBV (40 Hz 1.9 mm vertical displacement). Significant differences were found in the median frequencies, but not in the conduction velocity or signal amplitude. The observed changes are indicative of whole body vibration increasing the vastus lateralis muscle activity but not to a level indicative of physiological fatigue. These observations are of use to exercise and rehabilitation practitioners considering the use of vibration in exercise protocols.